2015
DOI: 10.1021/jacs.5b08748
|View full text |Cite
|
Sign up to set email alerts
|

The Many Faces of Heterogeneous Ice Nucleation: Interplay Between Surface Morphology and Hydrophobicity

Abstract: What makes a material a good ice nucleating agent? Despite the importance of heterogeneous ice nucleation to a variety of fields, from cloud science to microbiology, major gaps in our understanding of this ubiquitous process still prevent us from answering this question. In this work, we have examined the ability of generic crystalline substrates to promote ice nucleation as a function of the hydrophobicity and the morphology of the surface. Nucleation rates have been obtained by brute-force molecular dynamics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
281
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(304 citation statements)
references
References 131 publications
(366 reference statements)
22
281
1
Order By: Relevance
“…Our experiments show that only when synergetic cooperation of specific spatial arrangement of methyl groups (hydrophobic) and hydroxyl groups (hydrophilic) can lead to a pronounced promotion of ice nucleation (in the case of MpdAFP and MpAFP), whereas arrangement of merely hydroxyl groups leads to a modest or no obvious promotion of ice nucleation (type III AFP). These results obviously show that hydrophobicity is not the criterion for predicting the heterogeneous ice nucleation capacity of a surface, which is also recently suggested by some theoretical research groups (35,47,48). In combining with the MD simulation analysis, our work shows that the structure of interfacial water atop a specific solid surface, i.e., if it can facilitate the epitaxial growth of ice crystals, may be a good criterion for predicting the ice nucleation capability of this surface.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Our experiments show that only when synergetic cooperation of specific spatial arrangement of methyl groups (hydrophobic) and hydroxyl groups (hydrophilic) can lead to a pronounced promotion of ice nucleation (in the case of MpdAFP and MpAFP), whereas arrangement of merely hydroxyl groups leads to a modest or no obvious promotion of ice nucleation (type III AFP). These results obviously show that hydrophobicity is not the criterion for predicting the heterogeneous ice nucleation capacity of a surface, which is also recently suggested by some theoretical research groups (35,47,48). In combining with the MD simulation analysis, our work shows that the structure of interfacial water atop a specific solid surface, i.e., if it can facilitate the epitaxial growth of ice crystals, may be a good criterion for predicting the ice nucleation capability of this surface.…”
Section: Discussionsupporting
confidence: 55%
“…On the NIBF, irregular arrangement of hydrophobic/ hydrophilic groups and the existence of bulky hydrophobic groups and charged groups lead to the disordered structure. Depending on previous reports (35,39,40), the fraction of ice-like water molecules determines ice nucleation. This means that the IBF with hexagonal ice-like structured hydration layer promotes ice nucleation and the NIBF with disordered hydration layer depresses ice nucleation (41,42), which are consistent with our experimental observations.…”
Section: Significancementioning
confidence: 97%
“…Therefore, he suggested that the site for heterogeneous ice nucleation does not have to be ordered or, more particularly, does not have to possess a hexagonal geometry to match the structure of Ih. In a molecular dynamics study, Fitzner et al (2015) found that lattice match is at most desirable but not a requirement for heterogeneous ice nucleation.…”
Section: Lattice Match and Surface Chargementioning
confidence: 99%
“…Hu and Michaelides, 2007;Cox et al, 2012;Reinhardt and Doye, 2014;Zielke et al, 2015;Cox et al, 2015a, b;Fitzner et al, 2015;Pedevilla et al, 2016). To date there has been little overlap between work of this nature and laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%